Endoscopic Removal of a Cervical Esophageal Duplication Cyst. (11th October 2019) - Leader, Brittany A.; Rutter, Michael J.; Shott, Sally R.; Smith, Matthew M.
Abstract : A 6‐month‐old female presented for 2 months of noisy breathing. Flexible laryngoscopy showed limited bilateral vocal fold abduction. Computed tomography revealed a non‐enhancing 3.6 × 2.3 × 3.5 cystic prevertebral mass spanning C2‐T. Using an endoscopic approach, the overlying mucosa was incised, and the cyst was freed and fully excised from the surrounding mucosa with blunt microlaryngeal instruments without complication. Three months postoperatively she had no respiratory issues and was eating well. Flexible laryngoscopy revealed bilateral vocal fold mobility. We propose that endoscopic removal of a cervical esophageal duplication cyst in selected cases is an alternative to open excision. Laryngoscope, 130:2053–2055, 2020